REDESIGN OF ABDULRACHMAN SALEH AIRPORT AS A SMART AND GREEN TRANSIT NODE WITH A BIOCLIMATIC APPROACH - Dhea Farlin Arindita Zulfa; Hery Budiyanto; Septi Dwi Cahyani (ARCHITENSA : Architectural Design Journal, 2025)
Abdulrachman Saleh Airport is the only airport serving the Greater Malang area. It plays a significant role as the main “gateway” to a region known for its rich tourism, historical value, and natural potential. However, this “gateway” identity is not yet fully reflected in the physical character or the current terminal building. The terminal fails to create a strong impression as a representative entrance and lacks coherence in both character and design unity. Therefore, a redesign of the airport area is necessary to rebuild its visual and functional identity as a key transportation hub. This design adopts a bioclimatic approach to ensure the building responds to Malang’s climatic conditions while supporting the creation of a sustainable environment. The integration of smart building concepts is also applied to enhance spatial performance and efficiency through the use of environmentally friendly technology. Furthermore, the unification of the two terminal buildings into a single architectural identity becomes a key focus to improve accessibility for the passengers, visitors, and transportation modes. This strategy is expected to serve as a solution to the existing issues and strengthen Abdulrachman Saleh Airport’s role as an adaptive gateway that aligns with its surrounding environment and keeps pace with future development.